2020
DOI: 10.1186/s13287-020-01759-8
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of GATA4 enhances the antiapoptotic effect of exosomes secreted from cardiac colony-forming unit fibroblasts via miRNA221-mediated targeting of the PTEN/PI3K/AKT signaling pathway

Abstract: Background: GATA4 is an early cardiac-specific transcription factor, and endogenous GATA4-positive cells play a critical role in cardioprotection after myocardial injury. As functional paracrine units of therapeutic cells, exosomes can partially reproduce the reparative properties of their parental cells. Here, we investigated the cardioprotective capabilities of exosomes derived from cardiac colony-forming unit fibroblasts (cCFU-Fs) overexpressing GATA4 (cCFU-Fs GATA4 ) and the underlying mechanism through wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Contrary to the function of PI3K, PTEN reduces the activation of AKT and prevents all downstream signaling events regulated by AKT 54 . Evidence has confirmed the involvement of the PTEN/PI3K/AKT signaling pathway in the pathogenesis of many heart diseases, including coronary heart disease, chronic cardiac failure, and myocardial infarction (MI) 55 . Significantly, the PI3K/AKT pathway also plays a decisive role in the mechanism of heavy metal toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the function of PI3K, PTEN reduces the activation of AKT and prevents all downstream signaling events regulated by AKT 54 . Evidence has confirmed the involvement of the PTEN/PI3K/AKT signaling pathway in the pathogenesis of many heart diseases, including coronary heart disease, chronic cardiac failure, and myocardial infarction (MI) 55 . Significantly, the PI3K/AKT pathway also plays a decisive role in the mechanism of heavy metal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…54 Evidence has confirmed the involvement of the PTEN/PI3K/AKT signaling pathway in the pathogenesis of many heart diseases, including coronary heart disease, chronic cardiac failure, and myocardial infarction (MI). 55 Significantly, the PI3K/AKT pathway also plays a decisive role in the mechanism of heavy metal toxicity. Studies have confirmed that Cd exposure inhibited PI3K/AKT signaling pathway to induce cell apoptosis.…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…PTEN, a homolog of phosphatase and tension protein missing from chromosome 10, is an effective tumor suppressor that regulates cell growth and survival [ 25 , 26 ]. For instance, miR-221 has been reported to curb PTEN expression and activate phosphatidylinositol 3 kinase (PI3K)/AKT, thus repressing the apoptosis of cardiomyocytes (CMs) [ 27 ]. In addition, Per2 facilitates NHAC-kn inflammation in osteoarthritis by heightening the PTEN level and dampening the PI3K/Akt expression [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic expression of EZH2 in prostate cells can induce the transcriptional repression of a specific cohort of genes involved in prostate cancer [ 47 ]. GATA4 overexpression was shown to enhance the protective effect of cCFU-F-derived exosomes on myocardial ischemic injuries [ 48 ]. KCNC2 with tumor-specific alternative splicing is associated with the development of glioma [ 49 ].…”
Section: Discussionmentioning
confidence: 99%